Enhanced cytotoxicity of indenyl molybdenum(II) compounds bearing a thiophene function - Mrózek, Ondřej; Melounková, Lucie; Dostál, Libor; Císařova, Ivana; Eisner, Aleš; Havelek, Radim; Peterova, Eva; Honzíček, Jan; Vinklárek, Jaromír (Royal Society of Chemistry, 2019)
A series of six indenyl molybdenum compounds bearing a thiophenyl function in the side chain were prepared and characterized by analytical and spectroscopic methods. The structures of [(eta(5)-C9H6CH2C4H3S)(eta(3)-C3H5)Mo(CO)(2)] and [(eta(5)-C9H6CH2C4H3S)Mo(CO)(2)(bpy)][BF4] were determined by single-crystal X-ray diffraction. The compounds bearing N,N-chelating ligands exhibit increased cytotoxic activity against human leukemia cell lines MOLT-4; up to two orders of magnitude lower IC50 values were observed compared to analogues with unsubstituted indenyl, which clearly demonstrates the strong effect of the indenyl ligand modification on the biological activity of the molybdenum(ii) compounds. The highest cytostatic potential was observed for the complex bearing 4,7-diphenyl-1,10-phenanthtoline [(eta(5)-C9H6CH2C4H3S)Mo(CO)(2)(Ph(2)phen)][BF4] with IC50 (MOLT-4) = 0.19 +/- 0.02 mu M. Detailed regulation of the molecular and cellular mechanism by this derivative was investigated on the lung carcinoma cell line A549 and compared with the lung fibroblast cell line MRC-5. Rather unusual differences in the effects on tumor and non-tumor cell lines provide a unique insight into the cytostatic action of molybdenum(ii) complexes.
Zvýšená cytotoxicia indenylových komplexů molybdenu s thiofenovou funkční skupinou
Keywords: molybdenum complexes; cyclopentadienyl; cancer; p53; ligands; molybden; cyclopentadienyl; p53; ligandy